APPLICATIONS OF MACHINE LEARNING TO OPTIMIZE PLATE HEAT EXCHANGER PERFORMANCE - Imran, Ahmad Iqbal (Universiti Teknologi PETRONAS, 2021)
In industrial working area, heat exchangers have become one of the major equipment or units that must be operating at its best condition and performance.